2017
DOI: 10.1177/1073191117700723
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Youth Psychopathic Traits Inventory–Short Version in Justice-Involved and At-Risk Adolescents

Abstract: The current study examined the reliability and validity of the Youth Psychopathic Traits Inventory-Short Version (YPI-S) in two different samples of at-risk adolescents enrolled in a residential program ( n = 160) and at a detention facility ( n = 60) in the United States. YPI-S scores displayed adequate internal consistency and were moderately associated with concurrent scales on other self-report psychopathy measures and externalizing behaviors. YPI-S scores were moderately related to interviewer-ratings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…It should be noted that extensive research on this topic has demonstrated that psychopathic traits are multidimensional and can be indexed in childhood and adolescence (e.g., Andershed et al, 2018; Gillen et al, 2019; Kotler & McMahon, 2010; Muñoz & Frick, 2007; Salekin, 2017; Salekin & Lynam, 2010; Vitacco et al, 2003). Moreover, research has shown that psychopathy in youthful samples is linked to severe conduct problems, long-lasting psychosocial problems, delinquency, behavior maladjustment, as well as to various forms of aggressive behavior (AGG), including relational aggression, reactive aggression, and proactive aggression (e.g., Colins et al, 2018; Forth & Book, 2010; Frick et al, 2014; Salekin & Lynam, 2010; Vitacco et al, 2006; Wang et al, 2015).…”
mentioning
confidence: 99%
“…It should be noted that extensive research on this topic has demonstrated that psychopathic traits are multidimensional and can be indexed in childhood and adolescence (e.g., Andershed et al, 2018; Gillen et al, 2019; Kotler & McMahon, 2010; Muñoz & Frick, 2007; Salekin, 2017; Salekin & Lynam, 2010; Vitacco et al, 2003). Moreover, research has shown that psychopathy in youthful samples is linked to severe conduct problems, long-lasting psychosocial problems, delinquency, behavior maladjustment, as well as to various forms of aggressive behavior (AGG), including relational aggression, reactive aggression, and proactive aggression (e.g., Colins et al, 2018; Forth & Book, 2010; Frick et al, 2014; Salekin & Lynam, 2010; Vitacco et al, 2006; Wang et al, 2015).…”
mentioning
confidence: 99%
“…The 18‐item YPI‐S is an abridged version of the 50 item Youth Psychopathic Traits Inventory that was developed to minimise social desirability and response bias by ensuring that feelings and opinions are regarded as desirable competencies as opposed to deficiencies (van Baardewijk et al, ). The YPI‐S reportedly map onto the interpersonal, affective and behavioural domains of psychopathy across several countries, including Belgium (Colins, Noom, & Vanderplasschen, ), Italy (Fossati et al, ), Sweden (Colins & Andershed, ) and the United States (Gillen, MacDougall, Forth, Barry, & Salekin, ). In addition, the factors, which were invariant across gender (e.g., Colins et al, ; van Baardewijk et al, ), correlated significantly with variables such as aggression and delinquency (Fossati et al, ; Ray, Pechorro, & Gonçalves, ) and other self‐report measures of psychopathy (Gillen et al, ).…”
mentioning
confidence: 99%
“…The YPI‐S reportedly map onto the interpersonal, affective and behavioural domains of psychopathy across several countries, including Belgium (Colins, Noom, & Vanderplasschen, ), Italy (Fossati et al, ), Sweden (Colins & Andershed, ) and the United States (Gillen, MacDougall, Forth, Barry, & Salekin, ). In addition, the factors, which were invariant across gender (e.g., Colins et al, ; van Baardewijk et al, ), correlated significantly with variables such as aggression and delinquency (Fossati et al, ; Ray, Pechorro, & Gonçalves, ) and other self‐report measures of psychopathy (Gillen et al, ). Others have suggested that the YPI‐S is useful to assess for psychopathic behaviours in clinical settings (Gillen et al, ) and to document changes in psychopathic features from adolescence to emerging adulthood (Hawes, Mulvey, Schubert, & Pardini, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although short-forms may suffer from some psychometric limitations (e.g., attenuated validity coefficients) relative to their parent scales (see Credé, Harms, Niehorster, & Gaye-Valentine, 2012; Smith, McCarthy, & Anderson, 2000, for a review), instruments such as the YPI-S may be valuable for assessing psychopathic traits in contexts necessitating brevity (e.g., large-scale screening for psychopathic traits in community surveys), which are contexts that often raise concerns about inattentive responding. Of note, researchers have increasingly referenced the promising clinical utility of the YPI and YPI-S and begun to investigate the performance of these instruments in applied juvenile forensic contexts (Colins, 2016; Colins et al, 2017; Gillen, MacDougall, Forth, Barry, & Salekin, 2017). Perhaps due to this accelerating interest and knowledge base, the YPI-S has been incorporated into routine evaluations of juvenile offenders in applied settings (Vahl et al, 2014), suggesting the measure currently influences clinical decision-making in real-world contexts.…”
mentioning
confidence: 99%